2013
DOI: 10.1002/2013ja018780
|View full text |Cite
|
Sign up to set email alerts
|

Rippled quasi‐perpendicular collisionless shocks: Local and global normals

Abstract: [1] Proper determination of the shock normal is necessary for reliable determination of observed heliospheric shock parameters and comparison of observations with theory. The existing methods work sufficiently well for low and moderate Mach numbers one-dimensional stationary shocks. Higher-Mach-number shocks are no longer planar at the scales of the ion convective gyroradius or smaller. In rippled shock fronts, the local shock normal may differ substantially from the global normal. The former is determined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
31
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 46 publications
7
31
1
2
Order By: Relevance
“…This is presumably a typical feature of high Mach number shocks, in agreement with several past modeling studies of shocks (Burgess, ; Burgess & Scholer, ; Lowe & Burgess, ; Ofman & Gedalin, , ; Winske & Quest, ) as well as observations reported by (Johlander et al, ). In particular, Ofman and Gedalin (, ) discussed the deviation of the shock normal due to rippling, based on their 2‐D hybrid simulation study. The geometry of our observations is sketched in Figure , which shows the bow shock surface, with the electric field MVA normal in red at each spacecraft.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is presumably a typical feature of high Mach number shocks, in agreement with several past modeling studies of shocks (Burgess, ; Burgess & Scholer, ; Lowe & Burgess, ; Ofman & Gedalin, , ; Winske & Quest, ) as well as observations reported by (Johlander et al, ). In particular, Ofman and Gedalin (, ) discussed the deviation of the shock normal due to rippling, based on their 2‐D hybrid simulation study. The geometry of our observations is sketched in Figure , which shows the bow shock surface, with the electric field MVA normal in red at each spacecraft.…”
Section: Discussionsupporting
confidence: 91%
“…Individual normals deviated from the timing analysis normal by up to 30°. This is presumably a typical feature of high Mach number shocks, in agreement with several past modeling studies of shocks (Burgess, 2006;Burgess & Scholer, 2007;Lowe & Burgess, 2003;Ofman & Gedalin, 2013a, 2013bWinske & Quest, 1988) as well as observations reported by (Johlander et al, 2016). In particular, Gedalin (2013a, 2013b) discussed the deviation of the shock normal due to rippling, based on their 2-D hybrid simulation study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…They found that smaller and slower magnetic clouds can drive more corrugated shocks. In addition, several works using hybrid simulations [ Winske and Quest , ; Lowe and Burgess , ; Ofman and Gedalin , ] have shown that shock rippling occurs due to instability and/or surface waves inherent to the shock when the Alfvénic Mach number M A is >4.7. The scale of this rippling is of the order of the ion inertial length.…”
Section: Discussionmentioning
confidence: 99%
“…Early simulations were one dimensional in space and used hybrid particle‐in‐cell (hybrid‐PIC) algorithms [e.g., Leroy et al , ]. They soon moved to full particle simulations [e.g., Lembège and Dawson , ] and increased in dimensionality to 2‐D hybrid‐ and full‐PIC simulations [e.g., Lembège and Savoini , ; Savoini et al , ], gaining in complexity and detail of the physical description at large scales [e.g., Lin , ; Omidi et al , ; Blanco‐Cano et al , ] as well as for local kinetic processes [e.g., Ofman and Gedalin , ] and even reaching three spatial dimensions for hybrid‐PIC simulations of the magnetosphere [e.g., Lin and Wang , ]. PIC‐based methods suffer from the statistical noise inherent to the random sampling of the particle distribution injected in the simulation and the low number of particles that can feasibly be simulated.…”
Section: Introductionmentioning
confidence: 99%